2016
DOI: 10.1093/tropej/fmw015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Portable Haemoglobin Metre Performance in Children with Sickle Cell Disease and Implications for Healthcare in Resource-poor Settings

Abstract: Hb concentration determined by the portable testing system is comparable with that determined by the haematology analyser. We recommend its use as a point-of-care device for determining Hb concentration of SCD children in resource-poor settings where haematology analysers are not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…These observations make the POCT device ideal for use in SSA. 7,8,14,[20][21][22][23] Nothing drives home the reliability of the POCT for detecting and diagnosing HbSS among patients than its 100% agreement with the gold standard in this study. This high accuracy as found in this study, has also been previously reported regarding the performance of HemotypeSC among different study populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These observations make the POCT device ideal for use in SSA. 7,8,14,[20][21][22][23] Nothing drives home the reliability of the POCT for detecting and diagnosing HbSS among patients than its 100% agreement with the gold standard in this study. This high accuracy as found in this study, has also been previously reported regarding the performance of HemotypeSC among different study populations.…”
Section: Discussionmentioning
confidence: 99%
“…These observations make the POCT device ideal for use in SSA. 7 , 8 , 14 , 20 - 23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen studies (32%) reported challenges to POC(Hb)T use [13,15,19,29,31,32,47,49,50,54,55,58,60]. Overestimation of Hb concentration (n = 5) and errors in sampling and environmental factors (n = 5) were the most frequently reported challenges.…”
Section: Challengesmentioning
confidence: 99%
“…Difficulty in obtaining measurement/capillary sample in agitated children-can take longer to take measurement Rad-67 [58] HemoCue 801 [13] Aptus [49] 3 [15,19,54,58]. Specificity to detect anaemia and severe anaemia ranged from 70%-96.7% (median 84.7%, IQR: 6.1, n = 4) and 74.5%-100% (median 93.2%, IQR: 16.5, n = 7), respectively.…”
Section: Clinically Unacceptable Accuracymentioning
confidence: 99%